Bio-Inspired Algorithms (MDPI - Multidisciplinary Digital Publishing Institute, 2025)
The goal for this Special Issue on "Bio-Inspired Algorithms" was to seek original research papers about novel bio-inspired methods, analysis of already-existing techniques, or high-level practical applications from the field of computer science or any interdisciplinary field. We accepted manuscripts discussing evolutional (Genetic Algorithms, NSGA, etc.), swarm-intelligence-based (Particle Swarm Optimization, Ant Colony Optimization, Fireworks Algorithm, etc.), or brain-inspired computing (Neural Networks, Deep Learning, etc.) methods applied in any kind of research project (image processing, natural language processing, general optimization, physical simulations, etc.).